Adjunctive benefits of low-frequency transcutaneous electrical nerve stimulation for obesity frequent chronic conditions: a systematic review - Yu, An; Li, Xiang; Zhang, Wei; Zhang, Yazhou; Chen, Xi; Wang, Liuyan; Xie, Mei; Yang, Lei (Frontiers in Endocrinology, 2024)
Background： Obesity is widely recognized for its role in predisposing individuals to a spectrum of chronic health conditions. Emerging preliminary evidence points to the potential benefits of low-frequency transcutaneous electrical nerve stimulation (Lo-TENS) in enhancing various health outcomes among those with obesity and associated disorders.Objective: This systematic review was designed to assess the effectiveness of Lo-TENS for managing obesity and its related chronic diseases.Methods: For this systematic review, we included randomized controlled trials that evaluated the impact of Lo-TENS on individuals with obesity and its associated chronic diseases.Results: Eight trials encompassing 671 participants and spanning three unique populations: essential hypertension (EH), type 2 diabetes mellitus (T2DM), and obesity were deemed eligible for inclusion in this review. Compared to baseline measurements, Lo-TENS demonstrated a tendency to positively affect blood pressure in individuals with EH and metabolic parameters in those with T2DM. Nonetheless, the efficacy of Lo-TENS in treating obesity is not yet clear when contrasted with a no-intervention control group. When compared with other intervention modalities, three of the trials reported less favorable results.Although Lo-TENS did not consistently surpass other treatments or yield substantial improvements, it generally provided greater benefits than the majority of placebo controls. This suggests that Lo-TENS could potentially serve as a 4 4 beneficial adjunctive therapy in the management of obesity and its associated conditions. However, given the limited number of trials assessed, the elevated risk of bias within these studies, and the scarce evidence currently available, it is too early to reach definitive conclusions. Caution should be exercised when interpreting the current findings. There is an imperative for further high-quality research to thoroughly investigate and substantiate the efficacy of Lo-TENS in relation to obesity and its related disorders.